CAFF CBMP Report No.15 - Framework for a Circumpolar Arctic Seabird Monitoring Network - Arctic Council , Conservation of Arctic Flora and Fauna Working Group (CAFF, 2009)
Supporting Publication to the Arctic Council's CAFF Working Groups Circumpolar Biodiversity Monitoring Program